2011
DOI: 10.1002/cctc.201100206
|View full text |Cite
|
Sign up to set email alerts
|

The Iron‐Catalyzed Oxidation of Alkynes—1,2‐Dione Formation Versus Oxidative Cleavage—A Matter of Temperature

Abstract: The iron‐catalyzed oxidation of a variety of alkynes with hydrogen peroxide as the oxidant was examined in detail. Various reaction parameters were investigated in the oxidation of diphenyl acetylene. The best catalytic performance was observed for a combination of FeCl3 with 4‐dimethylamino pyridine (DMAP) as the ligand, yielding various 1,2‐diones in excellent yields and selectivities at room temperature. Moreover, by subsequently increasing the reaction temperature to 60 °C, a selective oxidative cleavage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…The research activity in the field led to a number of iron-based catalytic systems that can oxidize a number of organic substrates, utilizing oxygen, peroxides, or other oxidizing agents as the oxidant. Only two representative examples of this rich chemistry are depicted in Scheme 5 [66,67]. The field was pioneered by Grove, who, in 1979, found that iron porphyrin complexes can epoxidize alkenes and convert alkanes to alcohols, utilizing iodosylbenzene as the oxidant [25].…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…The research activity in the field led to a number of iron-based catalytic systems that can oxidize a number of organic substrates, utilizing oxygen, peroxides, or other oxidizing agents as the oxidant. Only two representative examples of this rich chemistry are depicted in Scheme 5 [66,67]. The field was pioneered by Grove, who, in 1979, found that iron porphyrin complexes can epoxidize alkenes and convert alkanes to alcohols, utilizing iodosylbenzene as the oxidant [25].…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…These results can be rationalized by mechanistic considerations (see below). However, the lower reactivity of alkynes with electron‐withdrawing substituents is a general problem that is observed in the oxidation of alkynes 5,11,14d,16. Likewise, aliphatic alkynes usually display lower reactivity to lead to modest yields.…”
Section: Resultsmentioning
confidence: 99%
“…However, the best results were obtained in refluxing dichloroethane, a solvent that is no longer used by the pharmaceutical industry 8. Iron catalysts have been reported since Sawyer's early work in 1990,9,10 and recently FeCl 3 (5 mol‐%)/H 2 O 2 was found to be an efficient catalyst for a room‐temperature oxidation of electron‐rich diarylalkynes 11. Recently, an interesting copper catalyst was disclosed that operates under mild conditions with O 2 /H 2 O as the oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction possibly proceeds by photo‐excitation of Ru(bpy) 3 Cl 2 , which is known to undergo single electron transfer (SET) in the presence of persulfate salt, thus generating sulphate radical anion (SO 4 •− ) and Ru III . On the other hand, phenylglyoxylic acid A generated in situ from phenylacetylene undergoes decarboxylation followed by hydrogen atom transfer (HAT) with sulphate radical anion (SO 4 •− ) to produce acyl radical B , and subsequently couples with protonated heteroarene C to give intermediate D . The final product 3 a is produced as a result of an SET reaction between intermediate D and Ru III , which also completes the photoredox catalytic cycle of Ru catalyst and hence its regeneration (Scheme ).…”
Section: Figurementioning
confidence: 99%